2021
DOI: 10.3390/microorganisms9112285
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Petroleum Hydrocarbons in Seawater: Prospects of Using Lyophilized Native Hydrocarbon-Degrading Bacteria

Abstract: This work aimed to develop a bioremediation product of lyophilized native bacteria to respond to marine oil spills. Three oil-degrading bacterial strains (two strains of Rhodococcus erythropolis and one Pseudomonas sp.), isolated from the NW Portuguese coast, were selected for lyophilization after biomass growth optimization (tested with alternative carbon sources). Results indicated that the bacterial strains remained viable after the lyophilization process, without losing their biodegradation potential. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Consequently, the bacterial progression with the utilisation of carbons and energy sources as diesel significantly degraded by the population, similar records were reported by another study (26). Moreover, soil contaminated with petroleum hydrocarbons should be kept properly to optimize the remediation of crude oil by microbes (54,55).…”
Section: Bacterial Growth Kinetic Studysupporting
confidence: 73%
See 2 more Smart Citations
“…Consequently, the bacterial progression with the utilisation of carbons and energy sources as diesel significantly degraded by the population, similar records were reported by another study (26). Moreover, soil contaminated with petroleum hydrocarbons should be kept properly to optimize the remediation of crude oil by microbes (54,55).…”
Section: Bacterial Growth Kinetic Studysupporting
confidence: 73%
“…Another study suggested that the use of pure cultures that provides practical advantage over the use of bacterial consortia or diversity by eradicating the ambiguity associated with constantly variation microbial diversification in case of community exploitation (24). Biodegradation of hydrocarbons through natural microflora allows for the bioconversion of hazardous compounds into relatively less or non-toxic forms that indicates as one of the primary-mechanisms through which petroleum, diesel and petro based products were mitigated from the eco-environment cost-effectively (10,20,(25)(26)(27). Most of bioremediation studies suggested using pure culture of the bacteria in a natural environment that remains unknown substantially (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method can significantly reduce the mass of the biopreparation. For example, studies have been carried out on the effect of the lyophilization stage on the viability of Rhodococcus cells and the possibility of their subsequent use in biotechnologies for cleaning environmental oil pollution [ 27 ]. The use of lyophilized cells made it possible to obtain 47% removal of total petroleum hydrocarbons after 15 days of the experiment.…”
Section: Introductionmentioning
confidence: 99%
“… Bioaugmentation Crude oil 14 80.64 Tian et al ( 2018 ) Oil-degrading bacterial population immobilized on biochar Bioaugmentation plus biostimuation TPH 60 58.08 Zhang et al ( 2019 ) Consortium (lyophilized two strains of Rhodococcus erythropolis and one Pseudomonas sp.) Bioaugmentation TPH 15 47 Perdigão et al ( 2021 ) Consortium ( Pseudomonas mendocina BPB 1.8, Bacillus cereus BPB 1.20, Bacillus cereus BPB 1.26, and Bacillus sphaericus BPB 1.35) Bioaugmentation plus biostimuation TPH 60 85 Napp et al ( 2022 ) Fungi (mycoremediation) Scopulariopsis brevicaulis PZ-4 Bioaugmentation Polyaromatic hydrocarbon (PAH)-aged soil 28 77 of total PAHs (phenanthrene (89%) and benzo[a]pyrene (75%)) Mao and Guan ( 2016 ) Penicillium citrinum Bioaugmentation Crude oil 23 77% (with individual alkane removal of 95%) Barnes et al ( 2018 ) Aspergillus sp. RFC-1 Bioaugmentation Crude oil 7 60.3% (with 97.4%, 84.9%, and 90.7% removal of naphthalene, phenanthrene, and pyrene resp.)…”
Section: Introductionmentioning
confidence: 99%